1999
DOI: 10.1111/j.1469-7998.1999.tb01193.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative biomechanics of an ophidian defensive behaviour: head triangulation in hognose snake (Heterodon) and an egg‐eating snake (Dasypeltis)

Abstract: Head triangulation is a regular component of the defensive behaviour of both Heterodon and Dasypeltis. In Heterodon platyrhinos, the triangulation is achieved primarily through rotation of the quadrate in the transverse plane with the distal end of the quadrate moving dorsad. The quadrate is pulled by the m. cervicomandibularis acting in conjunction with one of the jaw adductors. Head triangulation in Dasypeltis scabra is produced by rotation of the quadrate mainly in the frontal plane with the distal end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For example, coral snakes employ aposematic colour displays, while a number of other species have evolved neck flattening or "hooding" strategies, most notably known in cobras (Carpenter & Ferguson, 1977;Young, 1997;Young et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, coral snakes employ aposematic colour displays, while a number of other species have evolved neck flattening or "hooding" strategies, most notably known in cobras (Carpenter & Ferguson, 1977;Young, 1997;Young et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect hooding is viewed as similar to a variety of other ophidian visual displays that involve inflation or expansion of head and/or neck (e.g. Young et al, 1999;Young et al, 2000) The visual significance of the hood is further demonstrated by the presence in some species of eye spots or similar patterns on the dorsal surface of the hood (e.g. Wall, 1921).…”
Section: Efficacy Of Hooding Displaysmentioning
confidence: 99%